Mouthwashes in the Era of COVID-19: an Overview of Current Evidence - Arruda, José Alcides Almeida de; Souza, Vinícius Gomes; da Silveira, Márcia Maria Fonseca; Sobral, Ana Paula Veras; Moreno, Amália (ARCHIVES OF HEALTH INVESTIGATION, 2022)
The COVID-19 pandemic is evolving with additional studies on the pathogenicity of SARS-CoV-2 and its mechanism of spread, while current knowledge about the antiviral activity of available mouthwashes is largely based on the characteristics of similar coronaviruses. Since SARS-CoV-2 is spread through respiratory droplets, saliva, or direct contact, it is prudent to reduce the viral load in saliva and respiratory secretions. Thus, the viable and cost-effective measures that can be adopted and applied by the public and healthcare professionals to mitigate cross-contamination and transmission in the community are oral and throat hygiene. In this article, we bring together the evidence and mechanisms of all available mouthwashes against SARS-CoV-2. In addition, dental aerosols, transmission route and viral load were explored in the light of the literature. Different mouthwashes with specific activity against SARS-CoV-2 were investigated; however, the role of hydrogen peroxide and chlorhexidine gluconate as a pre-procedural mouthwash was ruled out. Nonetheless, the role of povidone iodine and, to some extent, cetylpyridinium chloride against SARS-CoV-2 was supported. We encourage researchers to consider involving different populations to verify the short- and long-term effectiveness of mouthwashes before using them as a community arsenal against the spread of COVID-19 infection.